Integration of Islamic Values in Children's Collection Selection Criteria: A Case Study at Al Azhar 30 School Library in Bandung - Rachmelya Salsabila Firdausy; Angga Hadiapurwa; Suci Yanti Ramadhan (Tibanndaru : Jurnal Ilmu Perpustakaan dan Informasi, 2026)
Purpose Research: This study analyzes the collection development process at the Al Azhar 30 Islamic School Library, Bandung, using the Evans & Saponaro (2005) model. It specifically examines how Islamic values are integrated into selection criteria and how collaboration occurs between the sole librarian and teaching staff. Research Method: A qualitative single-case study was employed. Data were gathered through in-depth interviews with librarian, participant observation, and documentation. Analysis Data: Data were analyzed using the interactive model by Miles, Huberman, and Saldaña (2014). Results: The findings reveal that the selection process follows a systematic flow from needs analysis to evaluation. Islamic values act as a "primary filter" to exclude content containing violence, sensuality, or doctrinal deviations. However, this process relies heavily on informal collaboration and "tacit knowledge" due to the absence of a formal written collection development policy. Conclusions: It is concluded that the internalization of religious values as tacit knowledge compensates for the absence of a written policy. The study recommends formalizing selection policies and establishing specific criteria for digital collections to meet modern educational needs. Keywords: children's literature, collection development, collection selection, islamic values, school library